2010
DOI: 10.1007/s00534-010-0278-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC5AC, an early marker of pancreatobiliary cancer, is regulated by DNA methylation in the distal promoter region in cancer cells

Abstract: Our results indicate that MUC5AC is regulated by CpG methylation and histone H3-K9 modification of the MUC5AC promoter distal region, but not by miRNAs. An understanding of the epigenetic regulation of MUC5AC may be of importance for the diagnosis of carcinogenic risk in the pancreatobiliary system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
(65 reference statements)
3
21
0
Order By: Relevance
“…The expression level of GAPDH mRNA in each cell line was used as a control in the RT-PCR analysis. The methylation pattern of each gene was consistent with the results of massARRAY analysis [2,4,6-10]. …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The expression level of GAPDH mRNA in each cell line was used as a control in the RT-PCR analysis. The methylation pattern of each gene was consistent with the results of massARRAY analysis [2,4,6-10]. …”
Section: Resultssupporting
confidence: 85%
“…Expression of mRNA was detected by semiquantitative RT-PCR analysis, with GAPDH mRNA used as a control. The expression level of mRNA shows a high propensity for regulation by DNA methylation [2,4,6-10] (Figure 3). The results of MSE analysis in each cell line (Figure 3) were consistent with DNA methylation patterns obtained by massARRAY analysis [2,4,7-10].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yamada et al showed that the CpG methylation status of around −3.7 kb in the MUC5AC promoter is associated with MUC5AC expression in some cancer cell lines, suggesting that the expression of MUC5AC is epigenetically regulated in the distal promoter region [45]. In fact, we found increase in MUC5AC expression by 5Aza-dC and/or TSA treatment, indicating some epigenetic mechanism involved in MUC5AC gene regulation (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Recently, methylated CpG mapping of MUC2 and MUC5AC promoters have been determined in pancreatic cancer cell lines [73,74]. It was shown that promoter methylation acts in combination with associated H3 histone deacetylation [74,75].…”
Section: Epigenetic Regulation Of Mucin Genes In Pancreatic Cancermentioning
confidence: 99%
“…It was shown that promoter methylation acts in combination with associated H3 histone deacetylation [74,75]. …”
Section: Epigenetic Regulation Of Mucin Genes In Pancreatic Cancermentioning
confidence: 99%